The role of generational diversity in enhancing employee competency development at Malaysia public universities: A literature review - Mohamed, Shahrulanuar; Abu Hassan, Mahadi; Ismail, Erwan; Suradi, Noorsaiyidah; Kudus, Norliah; Ab Rahman, Zaizul; Bakri, Mohammed Hariri (Human Resource Management Academic Research Society, 2025)
Generational diversity within organisations, particularly in higher education, is increasingly recognised as a critical factor influencing the development of employee competencies. Public universities in Malaysia face a pressing challenge: effectively managing this diversity to foster an inclusive and productive working environment. This study investigates the role of generational diversity in enhancing employee competencies and workplace dynamics in academic settings. By examining the interactions among different generations and the impact of their varying values and approaches on team collaboration and effectiveness, the research provides insights into how generational diversity shapes teaching, learning, and organisational performance. A systematic literature review of high-impact journal publications was conducted to explore the relationship between generational diversity and competency development. The findings reveal that generational diversity enriches perspectives in teaching and learning processes, while also influencing workplace dynamics and employee collaboration. Distinct generational approaches and beliefs are shown to drive innovation and improve educational outcomes. Moreover, the study highlights the importance of generationally sensitive management practices in enhancing job satisfaction and productivity. The results suggest that educational institutions should implement strategies to integrate generational diversity effectively, leveraging its potential to enhance competency development. Understanding and valuing generational differences are essential for creating an inclusive and competitive work environment, particularly in the context of Malaysian technical universities.